Analysis of Market Structure-Conduct-Performance of Gurame Fish (Osphonemus gouramy) in Kediri Regency - BJ Al Baiquni (Faculty of Fisheries and Marine Science, Brawijaya University, 2019)
The role of marketing institutions is important for conducting marketing activities, so that research has a purpose for: 1) knowing the market structure of gurame fish, 2) describing the behavior of gurame fish marketing institutions, 3) knowing the performance of marketing institutions for gurame fish in Kediri Regency. Type of research is descriptive using analysis of structure, conduct, and performance. Sampling techniques using purposive sampling and snowball sampling techniques, data collection techniques by observation, direct interviews and documentation. The results of the study are based on market structure that is influenced by the number of sellers and buyers, barriers to entry and exit markets, and market information indicating that the formed market structure is oligopoly; There are still many marketing agency behaviors that harm several parties in marketing such as accounts payable, and other fraudulent practices; The marketing of gurame fish in Kediri Regecy cannot be said to be efficient because of the uneven distribution of marketing margins, costs, and profits of each institution, as well as the high margin value, costs, and profits from one of the marketing institutions, large-scale collectors.